Mitochondrial chaperonin DNAJC15 promotes vulnerability to ferroptosis of chemoresistant ovarian cancer cells - Stefano Miglietta; Manuela Sollazzo; Iacopo Gherardi; Sara Milioni; Beatrice Cavina; Lorena Marchio; Monica De Luise; Camelia Alexandra Coada; Marco Fiorillo; Anna Myriam Perrone; Ivana Kurelac; Giuseppe Gasparre; et al. (Open Biology)
DNAJC15 is a mitochondrial TIMM23-related co-chaperonin known for its role in regulating oxidative phosphorylation efficiency, oxidative stress response and lipid metabolism. Recently, it has been proposed that the loss of DNAJC15 correlates with cisplatin (CDDP)-resistance onset in ovarian cancer (OC), suggesting this protein as a potential prognostic factor during OC progression. However, the molecular mechanisms through which DNAJC15 contributes to CDDP response remains poorly investigated. Here, we show that high levels of DNAJC15 are associated with accumulation of lipid droplets, decreased tumorigenic features and increased sensitivity to CDDP in OC cells. When overexpressed, DNAJC15 induced a phenotype displaying increased lipid peroxidation and subsequent ferroptosis induction. To prove a role for DNAJC15-induced ferroptosis in promoting sensitivity to CDDP, we reduced lipid peroxidation upon Ferrostatin 1 treatment, which decreased cells’ vulnerability to ferroptosis ultimately recovering their CDDP-resistant phenotype. In conclusion, our study uncovers the role of DNAJC15 in modulating ferroptosis activation and in the onset of CDDP resistance in OC cells.